Exploring the expectations, experiences and tensions of refugee patients and general practitioners in the quality of care in general practice. (23rd December 2021) - Patel, Pinika; Muscat, Danielle M.; Trevena, Lyndal; Zachariah, Dipti; Nosir, Hanaa; Jesurasa, Nishanthie; Hadi, Amina; Bernays, Sarah
Abstract: Background: Refugees and asylum seekers arrive in the Australian community with complex health needs and expectations of healthcare systems formed from elsewhere. Navigating the primary healthcare system can be challenging with communication and language barriers. In multicultural societies, this obstacle may be removed by accessing language‐concordant care. Emerging evidence suggests language‐concordance is associated with more positive reports of patient experience. Whether this is true for refugees and asylum seekers and their expectation of markers of quality patient‐centred care (PCC) remains to be explored. This study aimed to explore the expectations around the markers of PCC and the impacts of having language‐concordant care in Australian primary healthcare. Methods: We conducted semi‐structured individual in‐language (Arabic, Dari, and Tamil) remote interviews with 22 refugee and asylum seekers and 9 general practitioners (GPs). Interview transcripts were coded inductively and deductively, based on the research questions, using Thematic Analysis. Extensive debriefing and discussion took place within the research team throughout data collection and analysis. Results: Community member expectations of markers of PCC are constantly evolving and adapting based on invisible and visible actions during clinical encounters. Challenges can occur in the clinical encounter when expectations are 'unsaid' or unarticulated by both community members and GPs due to the assumption of shared understanding with language concordant care. Expectations of what constitutes satisfactory, quality PCC are dynamic outcomes, which are influenced by prior and current experiences of healthcare. Conclusion: This study highlights the importance of understanding that language concordant care does not always support aligned expectations of the markers of quality PCC between community members and their GP. We recommend that GPs encourage community members to provide explicit descriptions about how their prior experiences have framed their expectations of what characterizes quality PCC. In addition, GPs could develop a collaborative approach, in which they explain their own decision‐making processes in providing PCC to refugees and asylum seekers. Patient or Public Contribution: Bilingual researchers from multicultural backgrounds and experience working with people from refugee backgrounds were consulted on study design and analysis. This study included individuals with lived experiences as refugees and asylum seekers and clinicians as participants.